Analysis of the Implementation of Collaboration between PT. Gapura Angkasa and PT. IAS Support for the Adequacy of BCT (Baggage Cart) at Soekarno Hatta Airport, Tangerang - Banten - Gunardi, Gunardi; Dewantari, Aditya; Parman, Setyamartana (Ground Handling Dirgantara, 2025)
The availability of baggage carts (BCT) is a vital element in supporting passenger baggage and cargo services at Soekarno-Hatta International Airport. This study aims to analyze the implementation of the cooperation between PT Gapura Angkasa and PT IAS Support in fulfilling the requirement of 100 baggage cart units, as well as its impact on the adequacy of baggage carts for airport operational activities. A qualitative descriptive research method was employed, with data collected through observation, interviews, and document analysis. The findings indicate that the cooperation between the two companies has generally been effective in addressing the previous shortage of baggage carts by increasing the number of available units. This improvement has contributed to smoother ground handling operations and enhanced passenger baggage and cargo services. However, the study also identifies challenges in the distribution and deployment of baggage carts within the airport area. These challenges primarily stem from the lengthy bureaucratic procedures and strict regulations imposed by Angkasa Pura Indonesia regarding the entry of new assets into the airport, which delay the operational use of the carts despite the completion of the procurement process. Overall, the cooperation has played a significant role in fulfilling operational needs, although regulatory constraints remain a key obstacle to optimal implementation.